2020
DOI: 10.1002/aic.17031
|View full text |Cite
|
Sign up to set email alerts
|

Gas–liquid flows through porous media in microgravity: The International Space Station Packed Bed Reactor Experiment

Abstract: Experimental results on pressure drop and flow patterns for gas–liquid flow through packed beds obtained in the International Space Station with two types of packing are presented and analyzed. It is found that the pressure drop depends on the packing wettability in the viscous–capillary (V–C) regime and this dependence is compared with previously published results developed using short duration low‐gravity aircraft tests. Within the V–C regime, the capillary contribution is the dominant force contributing to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 21 publications
(26 reference statements)
0
18
0
Order By: Relevance
“…The flow patterns are discriminated by standard deviation, kurtosis, skewness, and domain frequency. Different pressure fluctuation sources are distinguished based on statistical analysis. …”
Section: Resultsmentioning
confidence: 99%
“…The flow patterns are discriminated by standard deviation, kurtosis, skewness, and domain frequency. Different pressure fluctuation sources are distinguished based on statistical analysis. …”
Section: Resultsmentioning
confidence: 99%
“…Experiments on gas-liquid flow through a packed-bed reactor performed under microgravity conditions at the International Space Station showed the presence of the so-called bubble and pulse flow regimes but noted the absence of the so-called trickle and spray flow regimes. [9][10][11] They found that the flow regime maps in microgravity differ from those under terrestrial gravity conditions, leaving a knowledge gap regarding the understanding of how gravity shapes the presence (or absence) of regimes in gas-liquid flow through a porous medium. High-fidelity simulations can bridge this gap.…”
Section: Discussionmentioning
confidence: 99%
“…We did not consider the effect of wettability in the present study, so contact angle dynamics were not modeled. We expect that the influence of the contact angle on flow dynamics is negligible in liquid continuous flow regimes, such as the bubble flow studied in this article 9 . In Section 3.3, unless otherwise stated, microgravity conditions (g=104m/s2) are considered in the simulations.…”
Section: Modeling and Simulation Methodologymentioning
confidence: 99%
See 2 more Smart Citations